PERANAN PENYIDIK PEGAWAI NEGERI SIPIL BALAI BESAR PENGAWAS OBAT DAN MAKANAN DALAM MENERTIBKANPEREDARAN OBAT TRADISIONAL YANG TIDAK MEMILIKI IZIN BERDASARKAN UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN DI KOTA PEKANBARU - Pantun Andrianus Lumban Gaol; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Traditional medicine is one of the treatment and care efforts in other ways outside of medicine and nursing. Traditional medicine is usually used drugs that made of traditional of materials - scholarly materials such as spices - spices or commonly known in Indonesia with the term "herbal" as traditional healing. medicine it self has wide - types, benefits and functionality to cure various disease. Traditional medicine is in demand by the community, especially the low income people, because traditional medicine itself than low cost, too easily obtained and its availability is not limited when compared to prescription drugs are relatively limited.Traditional medicine is generally used traditional medicine needs to be fostered and monitored by the government to be able to be directed to the treatment and care that can be justified efficacy and safety. The government in this case the Ministry of Health is responsible for the control and supervision of traditional medicine as stated in the Act - Act No. 36 of 2009 on Health and established official institutions non-departmental government (Officials) which is responsible to the President and coordinated by the Ministry of Health and Social Welfare called the Food and drug Administration, which carry out government duties in the field of food and drug supervision in accordance with applicable regulations.Every traditional medicine in circulation to go through the assessment process, testing and registration in advance. Assessment and testing of traditional medicine is intended to prove the efficacy, safe and reliable, helpful traditional medicine. Therefore unregistered prohibited imported, distributed, stored and consumed, so that traditional medicine is categorized as a dangerous and contrary to regulations. But the fact that many traditional medicine illegal unregistered and considered a dangerous drug, there is a kind of traditional drugs containing chemicals, drugs (BKO) and traditional medicines that do not have a marketing authorization which are sold freely on the market and in pharmacies - pharmacy-by in order to obtain profit for the people, thus leading to losses that can be fatal to those who consume them.Keywords: Role of Investigators - Marketing Authorization - Great Hall of Drug And Food